2021
DOI: 10.1101/2021.02.22.432340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A massive 7T fMRI dataset to bridge cognitive and computational neuroscience

Abstract: Extensive sampling of neural activity during rich cognitive phenomena is critical for robust understanding of brain function. We present the Natural Scenes Dataset (NSD), in which high-resolution fMRI responses to tens of thousands of richly annotated natural scenes are measured while participants perform a continuous recognition task. To optimize data quality, we develop and apply novel estimation and denoising techniques. Simple visual inspections of the NSD data reveal clear representational transformations… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 129 publications
(119 reference statements)
0
52
0
Order By: Relevance
“…Another potential limitation is that our findings are based on a single fMRI and image dataset, so it is not clear how well they would generalize to a broader sample of images. Given the explosive growth of the deep learning field [ 59 ] and the ever increasing availability of open brain imaging data sets [ 60 , 61 ] we see a furtive ground for the application of our approach in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential limitation is that our findings are based on a single fMRI and image dataset, so it is not clear how well they would generalize to a broader sample of images. Given the explosive growth of the deep learning field [ 59 ] and the ever increasing availability of open brain imaging data sets [ 60 , 61 ] we see a furtive ground for the application of our approach in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Although the organization of the dorsal third tier visual cortex remains to be further investigated in humans, the discontinuous representation of the anterior border of dorsal V3 has been seen in some individuals in published work from different labs (Allen et al, 2021;Van Essen and Glasser, 2018). Therefore, the ability of our model to predict the discontinuous representation of the lower vertical meridian at the anterior border of dorsal V3 suggests that this discontinuity is most likely a real structure-related variation, worthy of further investigation.…”
Section: Individual Variability In Retinotopic Mapsmentioning
confidence: 83%
“…Hlinka et al [37] only reported finding “subtle” nonlinear effects by, “testing across many pairs or even across many sessions.” In this study, we also found “subtle” yet significant nonlinear interactions by testing across a series of subjects. One potential avenue for future research might be to examine datasets comprising extensive scans of small numbers of participants [38]. Using many runs of single subject data and avoiding the averaging across subjects could increase the chances of identifying more subtle effects.…”
Section: Discussionmentioning
confidence: 99%